1989
DOI: 10.1126/science.2499044
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the Amyloid β Protein Precursor to Heparan Sulfate Proteoglycans

Abstract: any case their presence does not detract from the differences between the leukemic and remission samples of this patient. Miller et al. and Donti et al. suggest that the conclusions of our paper imply an understanding of the pathogenesis of APL or a direct association between rearranged MPO and critical DNA sequences involved in the t(15;17); this is not the case. Although questioned, it should be noted that only "one explanation for the presence of these novel bands in two of the M3 (APL) patients examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Potential sources of GAG which could support formation of a ternary complex with FXIa and PNII include cell-surface proteoglycans, solution-phase GAGs released from cell surfaces and cell-surface PNII. PNII has been reported to bind to heparan sulfate proteoglycan (27,59). Narindrasorasak et al (27) found that KPI-containing forms of APP bound with a K d of 9-10 nM and continued to bind to the core protein after heparitinase treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Potential sources of GAG which could support formation of a ternary complex with FXIa and PNII include cell-surface proteoglycans, solution-phase GAGs released from cell surfaces and cell-surface PNII. PNII has been reported to bind to heparan sulfate proteoglycan (27,59). Narindrasorasak et al (27) found that KPI-containing forms of APP bound with a K d of 9-10 nM and continued to bind to the core protein after heparitinase treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical evidence particularly implicates the HS proteoglycan 'perlecan' (Snow et al, 1994a,b). Curiously, the core proteins of both HS (Schubert et al, 1988) (however, see Gowda et al, 1989) and, more recently, chondroitin sulphate (CS) (Shioi et al, 1992) proteoglycans were claimed to be strongly related or identical to the APP itself. The ubiquitous distribution of HS proteoglycans (Herndon and Lander, 1990;Margolis and Margolis, 1993) and their functional involvement with important processes such as neurite outgrowth (Raulo et al, disaccharides by anion-exchange h.p.l.c.…”
Section: Introductionmentioning
confidence: 99%